A sustainability-oriented framework for the application of industrial byproducts to the base layers of low-volume roads. (1st May 2021) - Gomes, Guilherme J.C.; Magalhães, Adair J.; Rocha, Fabiano L.L.; Fonseca, Alberto
Abstract: Roadway engineering works typically rely on the utilization of natural aggregates as building materials. However, growing pressures for sustainable roads are highlighting the importance of replacing virgin materials with industrial byproducts. Constructors worldwide are trying to select optimum soil-byproduct mixtures that have a fair trade-off between engineering properties, environmental impacts and material costs. This requires a multi-objective analysis to explore feasible mixtures that honor a set of preferences to mathematically identify the best compromised soil-byproduct mixture. In this paper, a sustainability-oriented framework is proposed for selecting optimum soil-byproduct proportions for unbound base layers of unpaved roads. A compromise programming tool is implemented to select a mixture that is statistically preferred over mixtures with different byproduct contents. The method is illustrated using technical, economic and environmental indicators that are easily measurable. Investigations are performed for different decision-making perspectives including the constructor's, contractor's and the environment's viewpoints. Two byproducts from the steel industry are mixed in different proportions from 50% to 80% by weight with a clayey soil. The optimum mixture was obtained at a proportion of 70% byproduct and 30% clay. Monte Carlo simulations and sensitivity analysis of transport scenarios further supported this conclusion. Results demonstrate that mixture selection based only on strength properties provides inadequate optimum from a sustainable standpoint. The proposed framework can help road constructors incorporate environmentally-friendly materials in a cost-effective way, while maintaining the technical quality of base layers. Highlights: A sustainability-oriented framework is proposed to select optimum soil-byproduct mixtures for unpaved roads. The method adopts technical, economic and environmental indicators that are easily measurable. The decision-making includes the constructor's, contractor's and the environment's viewpoints. Mixture selection based only on strength properties provides inadequate optimum from a sustainable standpoint.